Different N6:N3 Ratios on Performance, Egg Quality, and Health of 81-Week-Old Laying Hens - Ganzaroli, J. F. [UNESP]; Ventura, G. [UNESP]; Polidoro, B. R. [UNESP]; Barbosa, B. F.S. [UNESP]; Lima, G. A. [UNESP]; Bello, H. J.S. [UNESP]; Polycarpo, G. V. [UNESP]; Araujo, R. G.A.C. [UNESP]; Polycarpo, V. C.C. [UNESP] (My University, 2022)
This study aimed to evaluate different n6:n3ratios on performance, serum biochemical variables, and egg quality in 81-week-old laying hens. A total of 224 laying hens, 81-week-old Hysex White, were utilized and distributed in a completely randomized design consisting of seven treatments and eight replications of four birds per cage, totaling 56 cages. The experimental treatments consisted of seven different n6:n3fatty acid ratios: 1.0:1.0, 2.0:1.0, 4.0:1.0, 8.0:1.0, 16.0:1.0, 32.0:1.0, and 64.0:1.0. For diet formulation, sunflower oil, rich in omega-6, and linseed oil, rich in omega-3, were used. Productive performance, egg quality and serum biochemical variables of laying hens were evaluated at the end of the cycle at 26, 27, and 28 days. Analysis of variance (ANOVA) was conducted and orthogonal contrasts were used to obtain the sum of squares of the treatment of the analysis of variance in polynomial regression effects. Egg quality variables did not vary significantly between the diets. Therefore, diet supplementation with polyunsaturated fatty acids at different ratios was possible without altering egg quality. The only exception was Haugh unit, which displayed a quadratic effect indicating that the best value was the n6:n3ratio of 32, according to data significance. It was concluded that an increase in n6:n3ratios decreases laying hens’ feed intake. The n6:n3 ratio of 34.64 provides greater eggs’ Haugh units, decreasing from that value on. The ratios of n6:n3 did not influence the hens’ serum biochemical variables.
Keywords: metabolism; oils; omega-3; omega-6; performance; Poultry